Counseling and Spiritual Assistance to Chemotherapy Patients: A Reflection in the Light of Jean Watson's Theory - Angelo Braga Mendonça; Eliane Ramos Pereira; Bruna Maiara Ferreira Barreto; Rose Mary Costa Rosa Andrade Silva (Universidade Federal do Rio de Janeiro, 2018)
Abstract Aim: To reflect on the use of spiritual interventions and methods of psychological, theological and psychotherapeutic counseling applicable to nursing. Method: Theoretical reflection article, used to identify approximations and distances of counseling methods and spiritual interventions with Jean Watson's Theory of Human Care. Results: The critical analysis of methods of psychological, theological and psychotherapeutic counseling indicates approximations with the Theory of Human Care, promoting the improvement of spiritual interventions directed to patients in chemotherapy. Conclusion: From Jean Watson's Theory emerged a creative, original and unique advice in nursing. Implications for practice: Understanding counseling methods and spiritual interventions are important tools for the practice of oncological nursing, as well as enhancing the resources available to integrate spirituality and health.